EMBEDDED DEVICE OPERATING SYSTEM - Zaitsev, S. A.; Kornienko, S. K. (Radio Electronics, Computer Science, Control, 2024)
Modern embedded operating system market analysis has been performed. Multitasking operating system kernel for embedded device control has been developed. Major embedded operating system functioning concepts has been described, embedded applications and driver programming model has been suggested.